2016
DOI: 10.1016/j.soilbio.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the legacy effect of previous forage crop and tillage management on soil biology, after conversion to an arable crop rotation

Abstract: The soil ecosystem provides a habitat for numerous and diverse fauna which hold a pivotal role driving decomposition and nutrient cycling. However, changing land use or management can alter population dynamics, changing soil biology within the system. The implementation of different field management can improve soil fertility, whilst natural variations in plant species growth and root system may create changes to soil structure and properties. All plant species create a legacy effect within the soil to some ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 49 publications
1
36
1
1
Order By: Relevance
“…Live earthworms were sorted into adults and juveniles, and identified to species using the taxonomic key by Sherlock () and functional groups following Roarty, Hackett, and Schmidt (). Other macrofauna abundance and diversity were also quantified from the soil block taken for earthworm sampling as per Crotty et al () ( n = 6), with macrofauna found identified to order and counted per block. This included centipedes, millipedes, beetles (adults and larva), fly larva, spiders, woodlice, slugs, and snails.…”
Section: Methodsmentioning
confidence: 99%
“…Live earthworms were sorted into adults and juveniles, and identified to species using the taxonomic key by Sherlock () and functional groups following Roarty, Hackett, and Schmidt (). Other macrofauna abundance and diversity were also quantified from the soil block taken for earthworm sampling as per Crotty et al () ( n = 6), with macrofauna found identified to order and counted per block. This included centipedes, millipedes, beetles (adults and larva), fly larva, spiders, woodlice, slugs, and snails.…”
Section: Methodsmentioning
confidence: 99%
“…Legacy‐associated plant residues may lead to the persistence of microbial groups which are best suited to utilize those (Allison et al., 2013). Previous research has also illustrated the legacy effect that differing species of grassland plants have various trophic levels of soil biology, that is, fungi, nematodes, mites, and earthworms, in a rotational agronomic system (Crotty et al., 2016; Detheridge et al., 2016). What is currently not clear, however, is the extent and the persistence of the influence imparted by different sward types (i.e., monocultures of different species and their mixtures) on soil bacterial and fungal community structure, and whether both constituents of the microbiome respond in a similar manner.…”
Section: Introductionmentioning
confidence: 99%
“…Crop fields, and to a lesser extent pastures and meadows, originate from natural or semi-natural environments which have been historically disturbed by mechanical (tillage), chemical (fertilizers, pesticides) and biological (vegetation change and seasonal collapse, grazing) practices (Green, 1989). However, these practices do not kill soil life, in particular the activity of ecosystem engineers (e.g., earthworms, enchytraeids), although in a constant state-of-change due to disturbances, is still visible (up to a certain threshold) in the form of aggregates and burrows, and continue to play a leading role in the maintenance of soil fertility through its control of soil microflora and other ecosystem services (Crotty et al, 2016;Fusaro, 2015;Van der Wal and De Boer, 2017;Wood et al, 2015;Lavelle et al, 2006). Litter is absent and cannot be used as a visual clue for characterizing the rate of recycling of organic matter, contrary to forests, heathlands and natural grasslands (Jenny et al, 1949).…”
Section: Resultsmentioning
confidence: 99%